2018
DOI: 10.1002/cb.1733
|View full text |Cite
|
Sign up to set email alerts
|

Understanding green purchase behavior through death anxiety and individual social responsibility: Mastery as a moderator

Abstract: This research proposes a framework to explore green consumption behavior from the perspective of the anxiety of death and individual social responsibility. Research data are collected from a sample of 280 consumers in Taipei, Taiwan. The findings reveal that consumers' anxiety of death affects consumers' green purchase attitude and then ultimately green purchase intention through the mediating variables of environmental concern and pro‐environmental behavior. On a similar line, individual social responsibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 59 publications
(136 reference statements)
6
52
0
Order By: Relevance
“…Consumer behaviours that are focused on harming the environment as little as possible (e.g., replacing your energy-lurking household appliance for an energy-efficient appliance, showering less long) or benefiting the environment (e.g.,refraining from purchasing Author Note: This research was supported by University of Bath research scholarship awarded to Dr Alina Mia Udall. environmentally harmful products, donating money to environmental charities) are typically regarded as "pro-environmental behaviour" (PEB; e.g., Gilal, Zhang, Gilal, & Gilal, 2019;Nguyen, Lobo, Nguyen, Phan, & Cao, 2016;Rahimah, Khalil, Cheng, Tran, & Panwar, 2018), as PEB is defined as those behaviours that "harms the environment as little as possible or even benefits the environment" (Steg & Vlek, 2009;p. 309).…”
Section: Consumer Behaviour As a Type Of Proenvironmental Pehaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer behaviours that are focused on harming the environment as little as possible (e.g., replacing your energy-lurking household appliance for an energy-efficient appliance, showering less long) or benefiting the environment (e.g.,refraining from purchasing Author Note: This research was supported by University of Bath research scholarship awarded to Dr Alina Mia Udall. environmentally harmful products, donating money to environmental charities) are typically regarded as "pro-environmental behaviour" (PEB; e.g., Gilal, Zhang, Gilal, & Gilal, 2019;Nguyen, Lobo, Nguyen, Phan, & Cao, 2016;Rahimah, Khalil, Cheng, Tran, & Panwar, 2018), as PEB is defined as those behaviours that "harms the environment as little as possible or even benefits the environment" (Steg & Vlek, 2009;p. 309).…”
Section: Consumer Behaviour As a Type Of Proenvironmental Pehaviourmentioning
confidence: 99%
“…An important way to reach a more sustainable society is to change individual consumption patterns among consumers (De Groot, Schubert, & Thøgersen, ; Schuitema & De Groot, ). Consumer behaviours that are focused on harming the environment as little as possible (e.g., replacing your energy‐lurking household appliance for an energy‐efficient appliance, showering less long) or benefiting the environment (e.g.,refraining from purchasing environmentally harmful products, donating money to environmental charities) are typically regarded as “pro‐environmental behaviour” (PEB; e.g., Gilal, Zhang, Gilal, & Gilal, ; Nguyen, Lobo, Nguyen, Phan, & Cao, ; Rahimah, Khalil, Cheng, Tran, & Panwar, ), as PEB is defined as those behaviours that “harms the environment as little as possible or even benefits the environment” (Steg & Vlek, ; p. 309). Therefore, the present research will focus on PEB, which includes a whole array of different consumer behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we determined that self-esteem mediates the effect of meaning in life on death in older adults. Humans’ reactions to death anxiety are dynamic and multifaceted [4, 57, 58]; therefore, additional mediating factors may influence the relationship between meaning in life and death anxiety. Other active elements may thus serve protective functions against death anxiety, such as attribution styles and dispositional optimism, and should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Doran and Larsen (2016) found that personal norms mediated between social norms and green purchasing behavioral intention. Rahimah, Khalil, Cheng, and Tran (2018) found that personal norms had significant positive effects on environmental concern and ultimately formed green purchasing intention. Attitude, attribution of responsibility, and social norms have been shown to directly activate personal norms.…”
Section: Literature Reviewmentioning
confidence: 99%